2022
DOI: 10.1111/bjd.21702
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders associated with lichen sclerosus: a case–control study in the All of Us Research Program

Abstract: Evidence for an association between thyroid-stimulating hormone and insulin-like growth factor 1 receptors: a tale of two antigens implicated in Graves' disease. J Immunol 2008; 181:4397-405. 4 Smith TJ, Hoa N. Immunoglobulins from patients with Graves' disease induce hyaluronan synthesis in their orbital fibroblasts through the self-antigen, insulin-like growth factor-I receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The current study did not find a significant association between thyroiditis and LS despite the already established relationship in women [ 28 ]. However, this study shows that patients with LS have an increased risk for thyrotoxicosis, which is in line with previous studies [ 27 ]. Lichen ruber planus is commonly found coexisting with LS lesions [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study did not find a significant association between thyroiditis and LS despite the already established relationship in women [ 28 ]. However, this study shows that patients with LS have an increased risk for thyrotoxicosis, which is in line with previous studies [ 27 ]. Lichen ruber planus is commonly found coexisting with LS lesions [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Their findings revealed that individuals affected by LS displayed a higher prevalence of being overweight or obese when compared to the broader Italian population [ 26 ]. An American study confirming older data suggested that autoimmune thyroid disease is more common in patients with LS with 2.67-, 2.88-, 2.34- and 2.05-fold increases in odds of having thyroiditis, autoimmune thyroiditis, hypothyroidism and hyperthyroidism, respectively [ 27 ]. The current study did not find a significant association between thyroiditis and LS despite the already established relationship in women [ 28 ].…”
Section: Discussionmentioning
confidence: 70%
“…In a case–control study of 765 cases of VLS, it was found a 2.88-, 2.34-, and 2.05-fold increase in odds of having autoimmune thyroiditis, hypothyroidism, and hyperthyroidism, respectively. This study provides further evidence that screening for thyroid disorders in LS patients should be considered ( 112 ).…”
Section: Associationsmentioning
confidence: 52%
“…In line with this, a study by Virgilli et al in Italy highlighted that LS patients exhibited a higher prevalence of overweight and obesity compared to the general Italian population [44,45]. Similarly, American research reinforcing earlier data demonstrated that autoimmune thyroid disease was more prevalent among LS patients, with significant increases in the odds of thyroiditis, autoimmune thyroiditis, hypothyroidism, and hyperthyroidism [11,42,43,46,47]. While one study did not establish a significant connection between thyroiditis and LS, particularly in women [42], our findings indicate an increased risk for both hyperthyroidism and thyroiditis in LS patients, aligning with the earlier mentioned studies.…”
Section: Discussionmentioning
confidence: 69%